A systematic review on the implication of Candida in peri-implantitis - Lafuente-Ibáñez de Mendoza, Irene; Cayero-Garay, Amaia; Quindós-Andrés, Guillermo; Aguirre-Urizar, José Manuel (International journal of implant dentistry, 2021)
Background Candida is a heterogeneous fungal genus. Subgingival sulcus is a refuge for Candida , which has already been related to the pathogenic inflammation of periodontitis. This work aims to review the presence of Candida in the sulcular fluid surrounding dental implants and discuss its potential role in peri-implantitis. Results A bibliographical research was performed in PubMed, Scopus and Web of Science databases, with the keywords candida , peri-implantitis, periimplantitis, “dental implant” and implant. Newcastle-Ottawa Scale was used to assess the methodological quality of the included studies. At the end, nine observational studies were included, which analysed 400 dental implants with PI and 337 without peri-implantitis. Presence of Candida was assessed by traditional microbiological culture in blood agar or/and CHROMagar, though identification was also detected by quantitative real-time PCR, random amplified polymorphic DNA or ATB ID 32C. Dentate individuals and implants with peri-implantitis (range, 3–76.7%) had a bigger presence of Candida . C . albicans was the most isolated species, followed by Candida parapsilosis , Candida tropicalis , and Candida dubliniensis . Conclusion Candida is part of the microbiological profile of the peri-implant sulcular fluid. More studies are needed to compare the link between Candida and other microorganisms and to discover the true role of these fungi in peri-implantitis.